2002
DOI: 10.1002/humu.9096
|View full text |Cite
|
Sign up to set email alerts
|

Missense mutations in the extracellular domain of the human neural cell adhesion molecule L1 reduce neurite outgrowth of murine cerebellar neurons

Abstract: Mutations in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…We interpret these findings as follows: the 200-kDa form is full-length fully glycosylated L1 as described in lysates from whole brain (Faissner et al, 1985;Michelson et al, 2002;Poltorak et al, 1995;Vawter et al, 1998). The protein in this band is immunoreactive with both antibodies to L1CD as well as L1ED, implying the full-length molecule is represented.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…We interpret these findings as follows: the 200-kDa form is full-length fully glycosylated L1 as described in lysates from whole brain (Faissner et al, 1985;Michelson et al, 2002;Poltorak et al, 1995;Vawter et al, 1998). The protein in this band is immunoreactive with both antibodies to L1CD as well as L1ED, implying the full-length molecule is represented.…”
Section: Discussionmentioning
confidence: 51%
“…However, that form would lack the cytoplasmic domain. Other possibilities include L1 without glycosylation (Michelson et al, 2002) or a proteolytic fragment containing the cytoplasmic domain cleaved by a protease present in adult CSF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This protein has been shown to be involved in axon guidance and fasciculation, and mutations in this gene reduce or abolish L1-dependent neurite outgrowth in vitro. 18 We observed that plexin B3 is an even more potent stimulator of neurite outgrowth when compared to L1. 8 Therefore, PLXNB3 may be considered an interesting candidate gene for the inborn variability in human-specific cognitive functions and brain volume.…”
Section: Discussionmentioning
confidence: 67%